Championing for a food secure community - Waswa, Boaz Shaban; Nchanji, Eileen Bogweh; Kimani, Owen Samuel; Muriithi, Catherine; Nyokabi, Miriam; Kagete, Eliud; Njagi, Irene; Micheni, Alfred N. (2023)
This video is a testimony of a farmer, Anne Wangari of Embu County in Kenya, on her learning experience under Ukama Ustawi. She shares how she has learnt about the crop diversification and resilient technologies and how this has empowered her to produce food and generate income. Anne is a voice for other women to embrace sustainable farming.